2020
DOI: 10.2981/wlb.00684
|View full text |Cite
|
Sign up to set email alerts
|

Predation costs and compensations in reindeer husbandry

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In an earlier study, the objective was identified -by the public authorities themselves -as promoting reindeer herding based on natural pastures (as opposed to feeding) . While this reconnects reindeer herding to landscape conditions, in its present interpretation it fails to include the impacts of other land uses (see below) and ignores that most of the cooperatives are already forced to use supplementary feeding as they no longer have access to natural winter pastures due to habitat loss and fragmentation (Forbes et al 2020;Pekkarinen et al 2020).…”
Section: The Narrative Of Sustainable Reindeer Husbandrymentioning
confidence: 96%
See 3 more Smart Citations
“…In an earlier study, the objective was identified -by the public authorities themselves -as promoting reindeer herding based on natural pastures (as opposed to feeding) . While this reconnects reindeer herding to landscape conditions, in its present interpretation it fails to include the impacts of other land uses (see below) and ignores that most of the cooperatives are already forced to use supplementary feeding as they no longer have access to natural winter pastures due to habitat loss and fragmentation (Forbes et al 2020;Pekkarinen et al 2020).…”
Section: The Narrative Of Sustainable Reindeer Husbandrymentioning
confidence: 96%
“…Predation has negative effects on herd productivity by changing the age structure of the breeding population, thus reducing calf production, and the opportunities for genetic selection. In the long run, this can compromise the economic sustainability of the livelihood (Pekkarinen et al 2020). The unpredictability of the work has increased, and the feeling of autonomy has decreased.…”
Section: Indirect and Long-term Effects Of Predatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wolverine is an opportunistic, facultative predator, with its diet in Finland varying from large ungulates to small rodents [ 12 , 13 ]. The wolverine’s distribution in northern Finland overlaps considerably with the reindeer husbandry area, and the high costs of predation in this area has led to conflict between humans and wolverines [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%